ANALISIS KESALAHAN PENGGUNAAN SIMPLE PAST TENSE PADA LEMBAR KERJA MAHASISWA: STUDI KASUS DALAM KELAS WRITTEN ENGLISH II - Luow, Andrila Kartika (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research, entitled â€œAn Error Analysis of Simple Past Tense in Studentsâ€™journals: A case study in Written English IIâ€ is an attempt to identify, classify and analyze the kinds of errors in the use of simple past tense in studentsâ€™ journalsÂ in written English II class. This research expected to help in developing language learning process and to give information in order to increase knowledge to understand errors made in the usage of simple past tense This research used a qualitative approach which has been done in several stages: preparation was made by reading the theory about simple past tense and the previous studies related to this research. Ellisâ€™s theory is used to explain how to analyze the use of simpleÂ past tense by students in written English II class. Data was taken fromÂ students in written English II class uses test which given by the teacher to the students to make a journal. The writer use some techniques of analyzing the data,as follows: Identification of error, Classification, Description,and Correction. The result of this research shows that there are three kinds of errors made by students; there are omission, misinformation and misordering. All the errors are generally caused by the lack of studentsâ€˜ ability of using the right English sentence patterns. The students can make the sentences but they do not know the correct patterns. Key word: simple past tense, error analysis, omission, misinformation and misordering.